"I've got to do this in a Southern": Stylized spoken literary quotation in the ELA classroom. (22nd September 2020) - LeBlanc, Robert Jean
Abstract: This article investigates whole‐class discussions of literature in the English classroom and the pragmatics of teacher interpretation in and through the voices of characters. In particular, it focuses on the whole‐class oral reading and discussion of the Tennessee Williams' play A Streetcar Named Desire in an ethnically and linguistically diverse rural Canadian classroom, and the teacher's stylized "Southern" oral performances of significant characters as part of her responses to student answers in whole‐class talk. Using extensive audio data from a 12th‐grade English class and drawing from the analytic tools of the linguistic anthropology of education, this article raises questions of the potential functions of stylized characters' voices in literary critical talk. This research contributes to ongoing conversations regarding the pragmatics of voicing, stylization, and the intersections of teacher talk and literacy learning in classroom discourse, with specific attention to the pedagogic work of enregistering bundles of linguistic features with particular teacher‐driven interpretive perspectives on literary characters.